The cinema of Tarkovsky : labyrinths of space and time - Skakov, Nariman, 1978- (KINO, the Russian cinema series., 2012)
The phenomenon of time was a central preoccupation of Tarkovsky throughout his career. His films present visions of time by temporal means - that is, in time. Tarkovsky does not represent time through coherent argument, Nariman Skakov proposes, rather he presents it and the viewer experiences the argument. This book explores the phenomenon of spatio-temporal lapse in Tarkovsky's cinema - from Ivan's Childhood (1962) to Sacrifice (1986). Dreams, visions, mirages, memories, revelations, reveries and delusions are phenomena which present alternative spatio-temporal patterns; they disrupt the line.